(untitled) (Journal of The Colloquium for Information Systems Security Education, 2023)
The rapid adoption of Software Defined Networking (SDN) in the industry has exposed certain security risks today some of which are unique to its paradigm. Security issues around the use-cases that expose these risks are fundamentally aligned with the networking and cybersecurity concepts that are taught at the graduate level in academia. In this paper, we present a number of lab activities on SDN security that are inspired from practical use-cases in SDN deployments. The goal of this effort is to help students give a shape to their thought process about the practical security implications of SDN deployments and gain valuable practical domain knowledge in securing an environment with such deployments.